Case of ovarian torsion-detorsion-ovarian and round ligament plication to save the ovary - Gangadharaiah, Mahendra; Vykuntegowda, Sunil Chikkatharahalli; Vijayalaxmi; Neelavani, Tejashwini A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Adnexal torsion is defined as twisting of the ovary and/or tube around usually the utero-ovarian ligament and in case of the ovary the infundibulopelvic ligament. Ovarian torsion is seen in reproductive age group, mainly due to enlongated ovarian ligament. Recurrence is more uncommon. This article presents a case of young 23-year-old women presenting with acute pain abdomen, with scan showing ovarian torsion, an emergency laparoscopy was performed, 1 turn of left infundibulopelvic ligament was noted and detorsion performed along with plication of round and ovarian ligament and utero-ovarian ligament plication. This helps in preventing recurrent ovarian torsion, though there is no standard management to prevent recurrent ovarian torsion, plications to some extent prevents recurrent torsion and thus also preserving fertility of women.